Analysis Of The Use Of Digital Payments In MSMEs As An Effort to Increase Income In The Sanggabuana Coffee Tourism Village - Rosmawati, Ery; Suherman, Ujang; Apriani, Zenita; Yani, Dini; Yudha Rahman, Shandikha Arya (Yayasan Pendidikan Belajar Berdikari, 2023)
Research in the Sanggabuana coffee village tourist area aims to analyze how digital payments are used by MSMEs based on indicators of the value of digitalization of MSMEs and by current conditions. This research also looks at the impact of using digital payments on increasing income. This research was carried out using a quantitative descriptive method, the results of the analysis show that MSMEs have a very high level of awareness, namely, 94% of MSMEs understand the importance of using digital payments in transactions. Where this level of awareness is related to the level of efficiency ( Efficiency ), security, and risk ( Security ), content related to digital payment finance is easy to understand ( Perceived ease of payment) and the use of digital payments provides benefits ( Perceived benefits) for MSME owners in developing their business and provide opportunities for business growth. However, the fact is that digital payment users among MSMEs in the Sanggabuana coffee village tourist area are relatively low. This can be seen from the percentage of digital payment users, namely 19 MSMEs or 63.33% do not use digital payments in transactions. This is in line with data from the Ministry of Communication and Information that the digital society index in Indonesia is classified as very low. From the research results, 36% of respondents who had provided digital payment facilities reported an increase in sales revenue every month.